La création d’une collection nationale de moulages en Belgique. Du musée des Plâtres à la section d’Art monumental des Musées royaux des arts décoratifs et industriels à Bruxelles - Valérie Montens (In Situ)
By the late 1830s, Belgium acquired plaster casts for its "Musée des plâtres". The creation in 1871 of the International Trade Commission allowed the development of a new series. Both collections were gathered in the late 1880s in the Museums of Decorative and Industrial Arts to form a panorama of the history of ancient sculpture. In the 20th century, priority was given to plaster casts which could be used for the teaching of arts and crafts, and to national heritage. After the First World War, the plaster casts lost their importance in the museums. The dismantling of the collection began in the early 1930s.